Joaquim Romero Magalhães and the History of Luso-Brazilian Cartography - Garcia, João Carlos (2019)
The History of Portuguese Cartography underwent strong development during the Estado Novo, within a framework of nationalist historiography, supporting colonial postulates. The old charts were presented as evidence of the leading role of Portuguese science during the Renaissance, and as proof of the primacy of the Portuguese geographic discoveries and the rights of colonial occupation and exploration of different territories. With the democratic regime, in the early 1990s, the future of this field of knowledge in Portugal was not quite auspicious. Only two small study groups interested in the History of Cartography coexisted at the University of Lisbon and at the Institute for Tropical Scientific Research. The studies and the diffusion of the History of Luso-Brazilian cartography gathered momentum in Portugal from the mid-1990s, with the presence of Joaquim Romero Magalhães (1942-2018) at the Comissão Nacional para as Comemorações dos Descobrimentos Portugueses, as Commissioner (1999-2002). His mission was to carry out the challenging task of "commemorating" the official arrival of the Portuguese navigators to South America. The "discovery of Brazil" and the relation between Portugal and Brazil, not only in the colonial period but also since the independence of that territory in 1822 to the present, were the major subjects for the organisation of great exhibitions, for publishing historical research works and primary sources, for granting scholarships, for the development of research projects, for organizing scientific meetings, for providing assistance to research centres. Under his supervision old maps and charts were always present in these events and works.